Permanent Shaft Repair Technology for Damaged Shield Segments in Operating Metro Tunnels - Fengyu LIAN; Gang CHEN; Linchuan LIAO; Wei HE (Chengshi guidao jiaotong yanjiu, 2024)
[Objective] During the drilling construction of ground surface dewatering shaft in a metro operational interval shield tunnel, the tunnel segments were damaged due to being pierced, resulting in sudden water hazards to interrupt metro service. In light of this, it is necessary to study permanent repair technologies for damaged shield segments within the operational metro tunnel. [Method] Considering the stability characteristics of the gravel and mudstone formations in the interval, a technology for repairing damaged segments in open-excavation vertical shaft is proposed, and this repair construction technology is elaborated in details. A finite element model is established to study the stress changes at the positions of the segment damage during different construction stages, including dewatering, vertical shaft excavation, segment repair, and vertical shaft backfilling. [Result & Conclusion] The minimum compressive stress after repairing the segment damage position is 0.732 MPa. With the backfilling of the vertical shaft, the stresses at the edge and the center of the repair site gradually increase. Ultimately, the stress stabilizes at around 2.124 MPa at the edge, and around 0.732 MPa at the center. Safety requirements are met, indicating that the repair technology is reliable.